STUDENT BEHAVIOR REFLECTION ON ONLINE LEARNING IN WETON PERSPECTIVE - Astrid Wangsagirindra Pudjastawa (Jurusan Sastra Indonesia, 2022)
This study aims to find and analyze the meaning of online learning according to the reflection of student behavior based on Weton. With a qualitative approach, this study collected data from 5 students. The results showed that student A (Monday Wage) interpreted the practice of online learning as an effort to beautify traditional learning, while student B (Monday Pon) interpreted it as violating obligations between teachers and students, Student C (Tuesday Pahing) interpreted it as a mere technique, Student D (Thrusday Legi) considers it a challenge, and Siswa E (Wednesday Pon) considers online learning to be a burden for teachers. The behavior of student A does not reflect his character, while the behavior of students B to E reflects his character. The condition of the family environment, the school environment at the previous level, experience, and always positive thinking are factors that influence the formation of his character.